Use of accelerometers in australian football to identify a kick - Ellens, S.; Blair, S.; Peacock, J.; Barnes, S.; Ball, K. (ISBS Proceedings Archive (Michigan), 2017)
The use of inertial measurement units (IMUs) is growing in elite sports such as Australian Football (AF). The purpose of this study was to identify ball contact (BC) and ball release (BR) of an AF kick and its intensity on the basis of IMU accelerometer data. A mechanical kicking limb, designed to replicate an AF kick, performed six punt kicks at six different angles. The acceleration dataset of each kick was analysed with Matlab and the characters BC and BR of the kick were obtained from high speed video footage and just over 43% was correct identified in the acceleration data. The kicks were correctly identified by Matlab as a kick. Kick intensity was obtained from the acceleration data. An AF kick identifier arose from this study. According to the findings, further analysis should analyse a kick with an accelerometer with a higher acceleration range.